Reducing Plastic Pollution in the Ocean: MycoBuoys as a Potential Solution - Van Hook, Sue (Maine Policy Review, 2023)
Natural mushroom mycelium-based MycoBuoys are an alternative to ubiquitous plastic flotation devices used in Maine aquaculture, fisheries and harbors. They fit perfectly into a circular economic model where natural resources are borrowed for a specific purpose and are returned as elements at the end of product life. MycoBuoys may be composted or used as mulch where 100% of the material enhances soil nutrients upon decomposition. In contrast to this cradle-to-cradle product, currently ubiquitous Stryofoam buoys have expensive end life costs in terms of ecosystem and organismal health consequences. Styrene is a known carcinogen, and the foam particles degrade into smaller fragments, but never go away. With the end of subsidies for fossil fuels (necessary to reach climate resilient goals), and with extended producer responsibility (EPR) for all manufactured products, plastic foams used for buoys will no longer be economically or environmentally feasible.
Keywords: MycoBuoys; Circular Economy; Buoy Alternative; Plastic pollution; oceans